ANALISIS PENGARUH PENGELOLAAN MODAL KERJA AGRESIF DAN KONSERVATIF TERHADAP PENDAPATAN RUMAH SAKIT - Laksono, Dwi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2010)
The short term asset and liability management like that working capital management have the important role to increase return and control the company risk. The hospital can adopt of working capital policy through aggressive-conservative management or both them seen in ratio of circulating assets to totalizing asset or in the form of defrayal policy in the form of ratio of current liabilities to high total liabilities. This research aim to know the conservative and aggresive working capital management influence to earnings measured from ROA and ROE hospital. Research conducted by using Data of BLU Hospital Balance and Activity Report in 2007 and 2008 get data from Result of Observing and Assessment of Governmental Hospital Financial Accounting System (PARSI) of per 31 December 2008 published by Health Departmental in 2008. Study technique use 2 technique that is descriptive analysis and multivariate analyse. Descriptive analysis used the statistic descriptive and multivarite analyse used the linear regression statistic. Result of the research find : 1) Increasing aggresive hospital in invesment have an signifikan effect to decreasing of hospital reveneu that measured by ROA, 2) Working capital management which increasing aggresive in invesment do not have an signifikan effect to increasing of hospital reveneu measured by ROE, 3) Aggresive progressively hospital in defrayal with the increasing of hospital acceptance measured by ROA, 4) Aggresive hospital in defrayal with the increasing of hospital acceptance measured from ROA.Â